PUBLIC ADMINISTRATION, ETHICAL INTEGRATION AND GLOBALIZATION - Ondrová, Drahomíra (European Integration Studies, 2017)
Globalization is a phenomenon which dominates our contemporary world in all spheres of our life. It is mostly evident in the economic and technological interconnections, in the fields of trade, financial sectors and mobility of capital and labor producing thus fastening of our interdependence not only in the field of commerce but at the same time networking our culture, habits, minds and way of our everyday lives. As it is expressed by Kimberly Hutchings the word “global” is generally used “to signify something pertaining to the world as a whole. If something has global causes or global effects, then the suggestion is that either its causes or its effects are worldwide” (HUTCHINGS, 2010: 2). With its positive as well as negative impacts and effects it touches all world regions, and sometimes it is difficult to distinguish between the local, regional and global. Deep influences are evident on the European Union as a whole influencing its big countries as well as smaller ones. At present the most depressing consequences of worldwide financial crisis are bringing excessively difficult burden especially on smaller countries, such as Slovakia, and terribly ostentatious effort on public administration attempting to moderate the most extreme depression consequences on their citizens.